Art portfolios in preschool teachers’ initial education as a means of acquiring professional competences and reflective practice - Županić Benić, Marijana (Revija za elementarno izobraževanje, 2025)
The study sought to examine the art portfolios of second-year undergraduate students of Early and Preschool Education at the Faculty of Teacher Education in Zagreb and their reflections on their own artwork. The aim was to examine how students experience, reflect on and interpret their creative work process. By reflecting, students acquire deeper understanding of art expression and perfect the ability to plan and evaluate visual art activities for implementation in their future work with children. The results show that students whose reflections on their own artwork through portfolios are more detailed show greater levels of self-awareness, creativity and pedagogical competence.
Keywords: likovno izobraževanje; portfelji; portfolios; Predšolska vzgoja; preschool teachers; professional competences; reflection; refleksija; strokovne kompetence; visual art education; Višje in visokošolsko izobraževanje; vzgojitelj predšolskih otrok